Determinación de hierro sérico proveniente de la ingesta de cápsulas que contienen sangre liofilizada de Gallus gallus domesticus - Mariños Melón, Fiorela Carol (2020)
The concentration of serum iron from the intake of capsules containing lyophilized blood of Gallus gallus domesticus was determined at different determined times (0h, 0.5h, 1h, 2h, 3h, 4h, 6h, 8h, 10h, 12h); through the spectrophotometric method with the Fer- color reagent. Chicken blood was obtained in a poultry market La Hermelinda, which was lyophilized to redose in capsules and then administer the 0.07g dose of lyophilisate to the 15 volunteers, who previously signed the informed consent. Subsequently, the blood samples were extracted at each established time, so that each of them was processed in a centrifuge and obtained serum, which was used to determine absorbed iron through the Fer Color reagent, which allows a change of color that allows the reading in the spectrophotometer (560nm), obtaining absorbances and then calculating the serum iron concentrations for each volunteer in each determined time. Finally, the serum iron concentration profile was obtained from the intake of capsules containing lyophilized blood of Gallus gallus domesticus; having concentrations at hour 0 of 123 μg/ dL, at half an hour of 475.33 μg/ dL, at the time of 618.44 μg/ dL, at 2h of 1003.64 μg/ dL, at 4h of 730.11 μg/ dL, 6h of 467.44 μg/ dL, 8h of 196 μg/ dL, 10h of 165 μg/ dL and 12h of μg/ dL Thus determining that the maximum concentration is 1003.64 μg/ dL and Produces the capsule with 0.7g of lyophilized blood of Gallus gallus domesticus at 2 hours after administration